DISCRIMINANT FACTORS AFFECTING IMPLEMENTATION OF MSME FINANCIAL STATEMENTS IN PADANG CITY (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2022)
The problem in this study is that MSMEs are often constrained by capital problems to develop their businesses. The government has provided a program on MSME financing, namely the People's Business Credit (KUR) in collaboration with banks. However, the realization of the KUR was far from the target because the bank appointed as the distributor was careful in lending. Where banks do not get adequate information related to the condition of MSMEs. The majority of MSME actors are unable to provide accounting information related to their business conditions. This means that MSMEs have not been able to measure the development of their businesses due to limitations in implementing the preparation of financial statements due to the low willingness of MSMEs in implementing financial statement preparation and the lack of knowledge and understanding of individuals in carrying out financial records. This study aims to obtain the factors that determine the influence of the implementation of the preparation of financial statements for MSME actors in the city of Padang. This research will be continued by using the R&D model through a practical financial report preparation module for MSMEs. However, it is necessary to know the determining factors in the implementation of the preparation of financial statements for MSMEs. The population in this study is MSMEs in the city of Padang. The samples used in this study were 3 sub-districts that had the largest number of MSME actors, namely Kuranji, Lubuk Begalung and East Padang districts. From the results of the study, it was found that the determining factor in the implementation of the preparation of financial statements is training. With the increasing frequency of training attended by business actors, it can improve the implementation of the preparation of financial statements. This factor is followed by reinforcement with experience and business size. As for education, it is meaningful when business actors have an education background in accounting and business, while research findings show that 75% of MSME actors do not have an educational background in accounting and business. It can be concluded from the results of the study that 45% of the determining factors in the implementation of financial statement preparation for MSMEs are determined by accounting and business training, experience and business size that guide MSME actors to implement financial report preparation as an evaluation tool and reference for formulating MSME sustainability policies.Keywords; Implementation of Financial Statements, Education, Experience, Training, Business Size